On Weakly Second Submodules - Saadi, Zainab; Ahmed, Ghaleb (Iraqi Journal of Science, 2019)
Let be a non-zero right module over a ring with identity. The weakly second submodules is studied in this paper. A non-zero submodule of is weakly second Submodule when , where , and is a submodule of implies either or . Some connections between these modules and other related modules are investigated and number of conclusions and characterizations are gained.